Improvement of Mathematical Problem Solving and Disposition Ability of MTs Students through StrategiesThink Talk Write in Cooperative Learning in Kuantan Singingi Regency - Guswinda, Guswinda; Yuanita, Putri; Hutapea, Nahor Murani (FKIP - Universitas Riau, 2019)
This research is motivated by the low both Mathematical Problem Solving Ability (KPMM) and Mathematical Disposition (DM) in solving problems of grade VII MTs students. This study aims to see an increase in KPMM and DM MTs students in Kuantan Singingi Regency. The form of research was quasi-experimental with pretest-posttest control group design. The population of the study was MTs students in Kuantan Singingi District with the sample being Grade VII students from 3 MTs in Kuansing. Data collection instruments in this study were KPMM tests and DM questionnaires. Data were analyzed using t-test, Mann- Whitney U test, one-way Anova. The results obtained were an increase in KPMM for students who treated with Think Talk Write (TTW) strategies in cooperative learning. They were higher than students who obtained learning with a scientific approach (g_TTW = 0.75> 0.61 = g_PS). So it appears that the increase in KPMM and DM students who get the TTW Strategy in Cooperative Learning is higher than students who get learning with a scientific approach.